Nano and microparticles as carriers for alveolar macrophage targeting in pulmonary tuberculosis therapy - Cunha, Ludmylla Costa (2019)
Tuberculosis (TB) is a leading infectious cause of death worldwide, even though a vaccine and several effective antibiotics are available for its prevention and treatment. Global TB control is very difficult due to various factors, including late diagnosis and patient non-compliance to long-term treatments, which leads to a high incidence of extensive resistance to effective anti-TB drugs. Overall, there are significant challenges associated with conventional TB therapy, including (i) drug resistance and toxicity; (ii) patient non-compliance, given the long-term therapy and severe side effects; (iii) and drug-drug interactions, particularly with antiretroviral drugs in patients co-infected with TB and HIV. Thus, the situation has come to a point where the development of novel intervention strategies is urgently needed. In this context, the pulmonary delivery of anti-TB drugs is a promising approach to treat lung TB. The disease represents approximately 80% of total cases, and thus the lung has been explored as an effective route for the delivery of drugs. This strategy not only allows targeting the infected organ instantly, but it can also reduce the systemic adverse effects of the antibiotics, which are main reasons for patient non-compliance. However, pulmonary drug delivery faces some limitations related with the proper airway structure, local degradation of drugs, and mucociliary clearance. In order to overcome some of these limitations of lung delivery, drug microencapsulation appears as a potential approach. In this sense, this work aimed at producing inhalable microparticles that efficiently associate two anti-TB drugs, isoniazid (INH) and/or rifabutin (RFB), for an application in pulmonary TB therapy. Fucoidan (FUC) and chitosan (CS) were the biomaterials selected to compose the matrix of the carriers. FUC is a polysaccharide composed of fucose units that has been reported to be specifically recognised by surface receptors of alveolar macrophages (the host cells of Mycobacterium tuberculosis). Likewise, CS is a polysaccharide composed of N-acetylglucosamine and D-glucosamine residues, the former being also specifically recognised by macrophages, according to the literature. This recognition by macrophages is believed to potentiate phagocytosis. The first approach involved the production of nanoparticles and it was considered that subsequent microencapsulation of the nanocarriers would be necessary to overcome aerodynamic limitations of nanosized carriers and their ability to reach the alveolar zone. Nanoparticles were spontaneously obtained by complexing FUC with CS, resulting from several formulations (polymeric mass ratio varying from 4:1 to 1:4). The produced unloaded FUC/CS nanoparticles presented average size range of 159 – 266 nm, PdI ranging between 0.21 and 0.36, and zeta potential varying from -39 mV to +12 mV, following the alteration of the mass ratios. The ability of FUC/CS nanoparticles to associate anti-TB drugs was assessed, and tests initiated with the incorporation of RFB, which was associated to obtain final polymer/drug mass ratio of 10/1 (w/w). Several attempts were made unsuccessfully, and therefore the work continued using another production method. Nanoprecipitation technique was then used, resulting in FUC nanoparticles and CS nanoparticles with mean size of 500 nm and 700 nm, respectively. However, the obtained nanoparticles showed little uniformity in size, indicated by PdI values, varying between 0.55 and 0.83. Moreover, an optimal protocol to obtain FUC- and CS-based nanoparticles that efficiently encapsulate INH and RFB could not be established. Taking into consideration the unsuccessful nanoparticle production and time restraints to accomplish the aims of the PhD plan, it was decided to focus the study on the development of polymeric microparticles. Microparticles were produced by spray-drying, associating the model drugs (INH and RFB), either separately or in combination. FUC microparticles effectively associated INH (95%) and RFB (81%), separately. Likewise, FUC microparticles loaded with the two anti-TB drugs simultaneously were also successfully produced, demonstrating high drug association efficiency (97% for INH and 95% for RFB). All FUC-based microparticles evidenced favourable aerodynamic properties for deep lung delivery upon inhalation. Single drug-loaded FUC microparticles showed aerodynamic diameter (MMAD) in the range of 2.0–3.8 μm. Likewise, the dual drug-loaded dry powder presented aerodynamic diameter of 3.6–3.9 μm. Overall, the formulations evidenced no cytotoxic effects on human alveolar epithelium cells (A549), although mild toxicity was observed on macrophage-differentiated THP-1 cells at the highest tested concentration (1 mg/mL). Nonetheless, this dose is considered overestimated compared to that effectively observed in vivo. The produced FUC microparticles also exhibited a propensity to be captured by macrophages or macrophage-like cells (target cells) in a dose-dependent manner. Particularly, dual drug-loaded microparticles displayed ability to activate the target cells and, moreover, effectively inhibited mycobacterial growth in vitro, preserving the bactericidal activity of the drugs. In vivo lung administration (BALB/c mice) of unloaded FUC microparticles indicated, in a preliminary assay, that the carriers induced no allergic responses. CS microparticles also associated INH (90%) and RFB (97%) efficiently, in separate formulations, whereas dual drug-loaded formulation resulted in 93% association efficiency for INH and 99% for RFB. All formulations presented adequate properties for deep lung delivery, with aerodynamic diameters ranging between 2.5 and 4 μm. Absence of toxicity was observed in human alveolar epithelium (A549 cells) but, as observed for FUC carriers, the highest tested concentration of microparticles (1 mg/mL) decreased the viability of macrophage-differentiated THP-1 cells upon 24 h exposure. This dose is however believed to be overestimated, as aforementioned. CS microparticles further evidenced strong ability to be internalised by macrophage-like cells (percentage of phagocytosis up to 99.9%), regardless of the dose. Yet, dual drug-loaded carriers induced macrophage activation and effectively inhibited the growth of mycobacteria in vitro. Moreover, the biomaterial (CS) was well tolerated by BALB/c mice upon pulmonary administration of unloadead CS microparticles. Overall, the obtained data gave positive indications on the potential of the proposed systems for an application as inhalable tuberculosis therapy.